Transplantation The Legality Of Human Organ Transplantation In Maqashidiah Perspective (A Study Of Fazlur Rahman’s Thought) - Khotijah, Siti; Zulfa, Imarotuz (ZAD Al-Mufassirin, 2024)
In the Qur'an, the prohibition of pigs is absolute, but the shari'ah realizes the preservation of Ḥifẓ an-Nafs (preserving life). Through an examination of Fazlur Rahman's thoughts, this study aims to look at the legality of transplantation through the eyes of contextual interpretation and contemporary Muslim thinkers. This research is literature research with qualitative method and sociology of religion approach. The purpose of shari'ah is to safeguard the interests of humans, damaging the honour of corpses is an individual benefit, while maintaining the safety of the living is a general benefit. Fazlur Rahman's understanding of deduction and induction states that reasoning starts from the specific to the general because that is the more general benefit that is prioritised. The benefits that can realise the five elements of the principle of the establishment of a law (Maqashid Sharia), namely the benefits that can protect religion, soul, offspring, mind, and property. The values of Maqashid Sharia are clearly illustrated in Fazlur Rahman's thoughts and decisions in punishing human organ transplants. This legality eliminates doubts in religion which indirectly eliminates doubts from an ethical point of view.